Computerized dynamic posturography in women with knee osteoarthritis - Hyoungjin Park (Asociación Española de Ciencias del Deporte, 2022)
The aim of this study was to compare the postural control of women with knee OA and healthy women peers and to determine the effect of knee OA on postural control. Thirty-two individuals, sixteen women with knee osteoarthritis and sixteen healthy women who were same age (± 3 yr), were evaluated on postural control as measured by a NeuroCom EquiTest. Outcomes included equilibrium scores, sensory analysis ratios, sway energy score, and latencies. Equilibrium scores (in condition 1: p=0.030, condition 3: p=0.019, condition 4: p=0.045, condition 5: p=0.010, condition 6: p=0.041, and Composite value: p=0.011), strategy score (Strategy 5: p = 0.015), sensory analysis ratios (VEST: p = 0.013 and PMAN: p = 0.023), and latencies (Largr_Forward: p=0.020 and Comp_latency: p=0.016) were significantly better in the healthy women group. The presence of knee OA had an impact on the sensory system's effectiveness and its utilization in postural control. Lower values of equilibrium scores, strategy scores, sensory analysis ratios for women knee OA group were evidence of larger displacements of the center of gravity in the forward-backward direction suggesting that women knee OA group was unable to maintain balance compared to healthy knee controls. Also, women with knee OA displayed a longer neuromuscular response latency to balance perturbations, indicating a reduced ability to begin in recover balance quickly following an unexpected disturbance. This observation should be taken into account in the fall prevention, especially, participants should place in dynamic situations with conflicted sensory environment, as these are found in daily life.